The Efficacy of Generic Imatinib in Treatment of Chronic Myeloid Leukemia - ديوب, آصف (Latakia University Journal -Medical Sciences Series, 2021)
Background: Chronic myeloid leukemia (CML) accounts for 15% of all adult leukemia, and is characterized by a translocation between chromosomes 9 and 22 (Philadelphia chromosome) and results in the mutant BCR-ABL gene. Most cases of chronic myeloid leukemia are diagnosed during the chronic phase, and in this case, tyrosine kinase inhibitors has increased survival and improved quality of life. The use of generic drug reduces costs and increases the chance of treating as many patients as possible. This study aim to evaluate the effectiveness of generic Imatinib in the treatment of chronic myeloid leukemia. Methods: This study is a retrospective study in a single center (Albaironi University Hospital in Damascus), we evaluate the hematological, chromosomal and molecular response in patients with chronic myeloid leukemia during the chronic phase and treated with generic Imatinib during 2009. Results: 28 patients were evaluated. A complete hematological response occurred after 3 months in all patients (100%). After 6 months, a major molecular response (MMR) occurred in 14 patients (50%) and a Complete cytogenetic response (CCyR) in 3 patients (10.7%). The response was studied after 12 months in 26 patients and a MMR occurred in 5 patients (19.2%) and a CCyR in 10 patients (38.5%). Conclusion: The use of generic Imatinib resulted in a hematological, chromosomal and molecular response and is effective in the treatment of chronic myeloid leukemia.